Effects of Salinity Stress at Reproductive Growth Stage on Rice (Oryza sativa L.) Composition, Starch Structure, and Physicochemical Properties - Yao, Dongping; Wu, Jun; Luo, Qiuhong; Zhang, Dongmeng; Zhuang, Wen; Xiao, Gui; Deng, Qiyun; Bai, Bin (Frontiers in Nutrition, 2022)
This study aimed to investigate the changes in polished rice composition, starch structure, and physicochemical properties from three rice cultivars treated with medium and high salinity stress at the reproductive growth stage. The results showed that salt stress led to poor milling and appearance quality, higher total starch content, protein content, higher proportion of the medium, and long chains of amylopectin, as well as gelatinization temperature (GT) but lower amylose content and lower proportion of the short chain of amylopectin. Compared with salt-sensitive cultivars, the salt-tolerant cultivars exhibited lower GT and gelatinization enthalpy, better pasting properties, and more stable crystal structure; therefore, their eating and cooking quality (ECQ) was less affected. The above results imply that salt stress at the reproductive growth stage can degrade ECQ and can slightly increase the pasting property of starch from salt-tolerant rice cultivar.